Pharmaceutical market assortment research of drugs for vaginal use with probiotic medicines detailing - Svitlana Aleinyk (Bogomolets National Medical University, 2021)
vaginal route delivery of drugs is an integral part of gynaecological diseases treatment including different genesis vulvovaginitis. The aim of this study it to analyze Ukrainian pharmaceutical market assortment of drugs for vaginal use with probiotic medicines determination. The marketing research was conducted with using of analysis, synthesis, comparison, generalization, content-analysis, statistical, graphical methods. The data of State register of medicines (as of June, 30, 2021), register of wholesale dispensing prices for medicines (as of June, 30, 2021), official web-sites LLC «Morion», «Pharmacy.online», «Compendium.online» were used as objects of the study. As a result, it is determined that as of June 30, 2021 142 medicines for vaginal use are registered on Ukrainian pharmaceutical market with dosage forms, active substances doses, condition for dispensing consideration, 100 brand names, 26 international nonproprietary names, 7 synonymous names. Structural ATC-classification analysis has shown that medicines for vaginal use are included in ATC-groups G «Genito urinary system and sex hormones» and D «Dermatologicals» The assortment macrocontour is formed, it demonstrates that 67,2% of drugs for vaginal use are involved in group G01A «Аntiinfectives and antiseptics, excluding combinations with corticosteroids». More than 80% of drugs for vaginal use are registered as solid dosage forms, and almost half of them as suppositories or pessaries. Almost 65% of medicines are foreign, and 3/4 of them contain only active substance, more than 50% are prescription only medicines. For 44,4% drugs for vaginal use the storage period of 3 years (36 months) is determined. Detailing analysis of medicines with probiotic activity has shown assortment deficiency (only 3 brand names are registered). The liquidity coefficients calculations for this brand manes don't allow to characterize these drugs as economically affordable. The obtained results of this study inform about the domestic drugs for vaginal use with probiotic activity development relevance, especially in pessaries as dominant dosage form on the pharmaceutical market.